Poroelastic behaviour of fine compacted soils in the unsaturated to saturated transition zone. (September 2015) - Lai, B.T.; Fabbri, A.; Wong, H.; Branque, D.
Abstract: The behaviour of quasi-saturated materials is important to consider when designing cuttings and embankments in which earthwork materials are compacted to the optimum proctor density. Under this condition, the in-pore gaseous phase takes the form of air pockets and bubbles embedded within the liquid phase, which significantly affects the overall behaviour of the soil. The assessment of highly saturated soils thus requires a precise understanding of hydro-chemo-mechanical couplings between the entrapped air, the in-pore liquid and the solid skeleton. This paper presents a fully coupled poromechanical model that separates the kinematics and the mechanical behaviours of the phases in their interactions with each other (e.g., liquid water, dissolved air, gaseous air and solid matrix). The assumptions about the entrapped air behaviour are defined from a bibliographic study, and linear elastic behaviour is used for both the liquid phase and the solid skeleton. The model is implemented in the FEM code COMSOL and is subsequently used to simulate oedometric tests under different loading paths: undrained compression or imposed liquid pressure variation at constant stress. The behaviour, which shows a continuous transition from unsaturated to saturated, is logical and consistent with available experimental data.